Open Government in the city of Córdoba, Argentina: a sensitivity regulation policy - Vaccaro, Natalia D. (2021)
This article aims at analyzing the meanings of the so-called open government (OG) from a communication approach articulated with social semiotics tools. Our hypothesis points out the impossibility to study these policies isolated from the urban social context where they are developed, making up a type of city and the citizens for such city. Our theoretical-methodological strategy is focused on approaching the OG as a sensitivity regulation device that establishes new ways of social control. The analysis will be conducted on the city of Córdoba, Argentina, whose urban population matrix and evaluating ideological environment legitimize these OG policies. Thus, from initially reconstructing the OG, we will try to understand its configuration and operation by setting up collective political and action scenes, creating a particular enunciation and visibility regime, establishing some possible practices and relationships, and defining a specific subjective type. The corpus of this study will consist of heterogeneous discursive practices: local media journalistic news and articles; municipal communications through official channels; and the OG website, the Portal de la Ciudad platform. The research period ranges from the launching of the municipal website in 2016 to its relaunch in 2018.